Privacy concern and perceived benefits towards privacy and election in Indonesia - Lubis, Muharman; Kartiwi, Mira (Institute of Electrical and Electronics Engineers, Inc., 2014)
As technology becomes one part of human lives to solve various problem, e-Voting offer the tremendous benefit to the society to celebrate the right in electing candidate with their own choice freely and responsibly. Despite its advantages, this celebration has great risks; challenges and threats regard the privacy of voters, which must be revealed, not only during the election but also before and after the election for several purposes. Thus, it should be some way for purpose of protection in one way or another. In this following decade as we can see from literature, the technology try as hard as can to answer this issue by several kind of protection methods, still further study need to be done to improve the solution offered. Therefore, the solution is not limited from technology side, we can also try to configure from different angle or perspective, such as from legal regulation protection or from social norm campaign. Thus, this study explain and suggests the need to put social norm as the middleware or mediator between IT perspectives while legal protection as supportive role in forming the alliance to deliver fundamental solution as the answer.